2022
DOI: 10.3390/su14042163
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Model of Internal Threats to Nuclear Security in Spent Fuel Reprocessing Plants Based on RDEU Theory

Abstract: The internal threat to nuclear security is one of the most serious problems in the physical protection supervision of spent fuel reprocessing plants. Both insiders and nuclear security departments have obvious characteristics of situational decision making and even irrational decision making. Combined with Game theory and RDEU theory, the RDEU Game model of insiders and nuclear security departments was constructed to analyze the existence of equilibrium solutions of two-way strategies under different emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…RDEU theory is a utility theory that considers the psychological preferences and emotions of decision makers and can measure the influence of emotions on decision making. Regarding this theoretical approach, Guo et al estimated the influences of heterogeneous emotions of government and individuals on the equilibrium strategy of an individual carbon trading scheme implementation model by constructing an RDEU evolutionary game model [49]; Ni et al combined game theory and RDEU theory to construct an RDEU game model of insiders and the nuclear security sector to study the existence of two-way strategic equilibrium solutions under different emotional states, and evaluated (from a dynamic perspective) the influence and change process of emotions on participants' decision-making behavior [50]; Liu et al used a static game, RDEU game, and sequential game to study the equilibrium strategies of emitters and stakeholders under different situations [51]; and Yang et al established a signaling game between miners (emotion-driven and judgment-driven) and managers from the perspective of emotional event theory to examine the effect of managers' emotions on miners' behavior [52]. It is evident that participant emotions have a significant impact on the behavioral decisions of decision makers.…”
Section: Game Theory and Research Progress Related To Subjects' Emotionsmentioning
confidence: 99%
“…RDEU theory is a utility theory that considers the psychological preferences and emotions of decision makers and can measure the influence of emotions on decision making. Regarding this theoretical approach, Guo et al estimated the influences of heterogeneous emotions of government and individuals on the equilibrium strategy of an individual carbon trading scheme implementation model by constructing an RDEU evolutionary game model [49]; Ni et al combined game theory and RDEU theory to construct an RDEU game model of insiders and the nuclear security sector to study the existence of two-way strategic equilibrium solutions under different emotional states, and evaluated (from a dynamic perspective) the influence and change process of emotions on participants' decision-making behavior [50]; Liu et al used a static game, RDEU game, and sequential game to study the equilibrium strategies of emitters and stakeholders under different situations [51]; and Yang et al established a signaling game between miners (emotion-driven and judgment-driven) and managers from the perspective of emotional event theory to examine the effect of managers' emotions on miners' behavior [52]. It is evident that participant emotions have a significant impact on the behavioral decisions of decision makers.…”
Section: Game Theory and Research Progress Related To Subjects' Emotionsmentioning
confidence: 99%
“…It was found that basic concepts are perceived differently by various security entities -security forces, scientific institutions, companies, and government institutions. The same concept can be perceived or defined identically, similarly, or even oppositely (Ni, Zou and Chen, 2022). The different perceptions of security concepts depended mainly on the field of human activity.…”
Section: Methodsmentioning
confidence: 99%
“…The evolutionary game theory has been applied in many research fields. For example, Ni et al [36] studied nuclear safety management based on the evolutionary game theory and Rank-Dependent Expected Utility theory. Huang et al [37] studied the incentive policy for assembled houses in China based on the evolutionary game theory.…”
Section: Evolutionary Game Theorymentioning
confidence: 99%